2008
DOI: 10.1016/j.apgeochem.2008.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Compartmentalization of physical and chemical properties in hard-rock aquifers deduced from chemical and groundwater age analyses

Abstract: International audienceUsing groundwater age determination done through CFC analysis and geochemical data obtained from seven sites in Brittany (France), a hydrogeochemical model for hard-rock aquifers is presented. According to the geological structure, three zones can be defined: the weathered layer, about 30 m thick; the weathered-fissured layer (fractured rock with a high density of fissures induced by weathering), which represents a transition zone between the weathered zone and the lower fractured zone; a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
100
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 109 publications
(105 citation statements)
references
References 76 publications
4
100
0
1
Order By: Relevance
“…The analytical uncertainty is estimated to be 1% to 3% for CFCs and near 5% for SF 6. Thus, the global uncertainty on residence time, including sampling, analysis, selection of the recharge temperature in Henry's law, and dispersion-adsorption effects, is estimated to be from 2 to 11 a (Ayraud et al, 2008;Labasque et al, 2006;Labasque et al, 2014).…”
Section: Dating Tracers Excess Air and Recharge Temperaturementioning
confidence: 99%
See 2 more Smart Citations
“…The analytical uncertainty is estimated to be 1% to 3% for CFCs and near 5% for SF 6. Thus, the global uncertainty on residence time, including sampling, analysis, selection of the recharge temperature in Henry's law, and dispersion-adsorption effects, is estimated to be from 2 to 11 a (Ayraud et al, 2008;Labasque et al, 2006;Labasque et al, 2014).…”
Section: Dating Tracers Excess Air and Recharge Temperaturementioning
confidence: 99%
“…The calculations assume an average elevation for the samples of 100 m ASL. Excess air calculation is used to correct SF 6 data, which could be greatly influenced by this parameter in contrast to CFCs (Ayraud et al, 2008;Maiss and Brenninkmeijer, 1998;Plummer et al, 2001). …”
Section: Dating Tracers Excess Air and Recharge Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…2). Moreover, previous studies in the Armorican basement have identified a compartmentalization of these crystalline rock aquifers from hydrological, geochemical, geological and geophysical data (Ayraud et al, 2008;Roques et al, 2014), and from regional-scale numerical modeling (Goderniaux et al, 2013). Geochemical studies also showed specific chemical compositions of the water in the deep fractured aquifer, potentially including saline groundwaters Ayraud et al, 2008;Pauwels et al, 2013).…”
Section: Hydrogeological Settingmentioning
confidence: 98%
“…The study focuses on the Armorican basement (western France), where several authors have reported evidence of saline fluids (Ayraud et al, 2008;Pauwels et al, 2010). Three main transgressions were recorded during Mio-Pliocene to Pleistocene times, the latest being the highest.…”
Section: Introductionmentioning
confidence: 99%